The inner CSF–brain barrier: developmentally controlled access to the brain via intercellular junctions - Whish, Sophie; Dziegielewska, Katarzyna M.; Møllgård, Kjeld; Noor, Natassya M.; Liddelow, Shane A.; Habgood, Mark D.; Richardson, Samantha J.; Saunders, Norman R. (Frontiers in Neuroscience, 2015)
In the adult the interface between the cerebrospinal fluid (CSF) and the brain is lined by the ependymal cells, which are joined by gap junctions. These intercellular connections do not provide a diffusional restrain between the two compartments. However during development this interface, initially consisting of neuroepithelial cells and later radial glial cells, is characterized by “strap” junctions, which limit the exchange of different sized molecules between CSF and the brain parenchyma. Here we provide a systematic study of permeability properties of this inner CSF-brain barrier during mouse development from embryonic day, E17 until adult. Results show that at fetal stages exchange across this barrier is restricted to the smallest molecules (286Da) and the diffusional restraint is progressively removed as the brain develops. By postnatal day P20, molecules the size of plasma proteins (70kDa) diffuse freely. Transcriptomic analysis of junctional proteins present in the CSF-brain interface showed expression of adherens junctional proteins, actins, cadherins and catenins changing in a development manner consistent with the observed changes in the permeability studies. Gap junction proteins were only identified in the adult as was claudin-11. Immunocytochemistry was used to localize at the cellular level some of the adherens junctional proteins of genes identified from transcriptomic analysis. N-cadherin, β– and α-catenin immunoreactivity was detected outlining the inner CSF-brain interface from E16; most of these markers were not present in the adult ependyma. Claudin-5 was present in the apical-most part of radial glial cells and in endothelial cells in embryos, but only in endothelial cells including plexus endothelial cells in adults. Claudin-11 was only immunopositive in the adult, consistent with results obtained from transcriptomic analysis. These results provide information about physiological, molecular and morphological-related permeability changes occur